The Heart of Seminary Life: An In-Depth Exploration of Integrating Spirituality into All Aspects of Seminary Formation - Giangan, Bernie; Laranjo, Juniel; Selgas, Jinggle (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2025)
The study examines how spiritual formation is integrated into various aspects of seminary formation, which leads to answer the main question